Analytical and quantitative assessment of the state of the spleen and immune processes in rats under administering Vipera berus venom - Bobr , A.M. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. The spleen can maintain the body's stability in response to the physical and chemical factors of the environment. However, the organ's immune status reserves suffer significantly under their chronic influence. They are depleted due to violating the morphology and functions of key structural elements. In this regard, more and more scientific studies are focusing on the pathophysiological pathways of spleen damage under the influence of adverse factors of various genesis. Objective. Determination of morphometric parameters of changes in the spleen of rats under the influence of Vipera berus venom. Methods. To assess the toxic effect of the venoms of Vipera berus berus and Vipera berus nikolskii snakes on the general morphology of the spleen and the manifestation of antigen-dependent immune processes in it, we compared discrete and continuous variables in rats from the control and two experimental groups. Results and conclusion. It was established that the pathological effect of Vipera berus nikolskii venom on the red pulp leads to a set of processes that increase its total area, thus equalising the ratio of white pulp to red pulp in this group. The most pronounced increase in the share of lymph nodes relative to the red pulp is in rats exposed to Vipera berus berus poison, indicating intensive lymphocyte proliferation processes precisely under the influence of this toxin. The hemolytic solid effect of the venom of Vipera berus nikolskii leads to the destruction of formed blood elements and the accumulation of their particles, which are also phagocytised by macrophages. This adds another load factor to phagocytising cells, leading to their overload and disruption of the normal processes of metabolism and exocytosis.